Get out [videorecording (DVD)] - Peele, Jordan, 1979-; Kaluuya, Daniel, 1989-; Williams, Allison, 1988-; Whitford, Bradley (Universal Pictures Home Entertainment, 2017)
A young black man meets his white girlfriend's parents at their estate, only to find out that the situation is much more sinister than it appears.